Toxicity of pesticides with fungicide and fungicide + insecticide effects to Eisenia Andrei Toxicidade de agrotóxicos de efeito fungicida e fungicida + inseticida em Eisenia andrei - Giordani I.A. (2020)
© 2020, Institute for Environmental Research in Hydrographic Basins (IPABHi). All rights reserved.Pesticides are widely used in the agricultural sector to control and prevent pests and diseases. The use of these products can adversely affect non-target organisms that have a significant role in the soil, such as earthworms. This study evaluated the toxicity of the commercial formulation of the fungicide Comet® (active ingredient - a.i. pyraclostrobin) at concentrations of 0.08, 0.17, 0.35, 0.70, 1.40 and 2.80 mg of the commercial formulation kg-1 soil and the fungicide + insecticide Standak®Top (a.i. pyraclostrobin + thiophanate-methyl + fipronil) at concentrations of 0.05, 0.10, 0.20, 0.60, 1.20 and 2.40 mg of the commercial formulation kg-1 soil, plus the control treatment, to Eisenia andrei in Tropical Artificial Soil (TAS) by means of standardized tests.